SPATIOTEMPORAL BEHAVIOR AND NEW DISTRIBUTIONAL RECORD OF SUBFAMILY HEMIACRIDINAE (ACRIDIDAE: ORTHOPTERA) FROM AZAD JAMMU AND KASHMIR, PAKISTAN - Z. M. Sarwar; A. Tamkeen; M. R. Khan; Z. Hussain; M. S. Asghar; M. A. Badar (Journal of Animal and Plant Sciences, 2023)
Members of order Orthoptera are considered one of the most important groups of phytophagous insects. Indeed, many members of this group are considered serious pests of row and forage crops and often are in direct competition with vertebrate grazers. The present study was conducted to explore the species diversity, composition and spatiotemporal behavior of subfamily Hemiacridinae from different areas of Azad Jammu and Kashmir. Specimens were collected with the help of ariel insect net. Six species of subfamily Hemiacridinae of two genera i.e. Parahieroglyphus and Hieroglyphus were described. Three species, H. banian, H. annulicornis, and P. bilineatus have a new distributional record from study area. In the case of spatiotemporal behavior, the maximum temporally population was observed in September from district Kotli. Hieroglyphus banian, H. nigrorepletus, and H. concolor were found abundantly in September while P. bilineatus and H. oryzivorus population were maximum in October from the study area. Overall, results suggest a potential of acridid grasshoppers to contribute to the native communities and provides information about the ecology and population dynamics of grasshoppers for future research to enhance the sustainable management of this major diverse pest.
Keywords: Spatiotemporal behavior; Hemiacridinae; Grasshopper; New record; Azad Jammu & Kashmir